Endoscopic incision of rectal diverticulum: A case report - Qiu, Yan-Yu; Cheng, Yong; Dong, Peng; Hu, Deng-Hua; Shu, Xin-Peng; Wen, Guang-Xu (Zeitschrift für Gastroenterologie, 2022)
A 70-year-old woman with a rectal diverticulum presented with anal pendant expansion and difficulty in defecation for more than 1 year. The patient was diagnosed with a rectal diverticulum by pelvic enhanced magnetic resonance imaging (MRI), computerized tomography (CT), rectal angiography, and colonoscopy. The endoscopic diverticulum incision procedure (EDIP) was implemented with this patient. At the 4-month follow-up, anal pendant expansion and difficulty in defecation were significantly relieved. Furthermore, colonoscopy proved that there were no vestigial feces in the diverticulum.
Keywords: Rektaldivertikel; Fallbericht; endoskopische Therapie